Colombian business and logistics environment by the year 2020 - Ojala, Elina (My University, 2021)
This thesis aimed to provide information on Colombia’s business and trading environment for companies interested in the market. The main focus of the analysis was on logistics performance. To put Colombia’s business and logistics environment in perspective, its performance was compared with that of its Latin American peers. An important concept for the context of this thesis is trade and transport facilitation (TTF), which means improving efficiency and reducing costs of moving goods across borders. This notion as well as indicators for assessing countries’ TTF performance are introduced in the theoretical framework. Also, studies on determinants of logistics performance are reviewed. Two types of factors were identified to affect countries’ logistics performance: infrastructure and institutional quality. These two types of indicators were used in the analysis of this thesis. The research approach selected for this study is descriptive and qualitative, as the objective was to create a comprehensive description of the Colombian business environment. The analysis consists of an outlook on Colombia’s economy and transport sector as well as on TTF performance in international evaluations. The research data included reports, statistics, and international rankings. The research framework is unique because it combines a transport sector analysis with a greater number of TTF indicators than seen in previous studies. The analysis covering data till the year 2020 showed that despite being ranked as one of the best business environments in Latin America, Colombia’s competitiveness is hindered by poor road and railway infrastructure, border management issues, corruption and insecurity. In turn, connectedness by air and sea as well as seaport infrastructure are very good. The US market is easily reached by air. Colombia enjoys the advantage of having access to both the Atlantic and the Pacific. It also has an extensive system of navigable rivers. However, port infrastructure in the Pacific is underdeveloped and rivers are currently not used at their full potential. Significant infrastructure projects have been planned for the 2020s, including increasing the cargo capacity of the rivers and developing inactive railways to create efficient intermodal transport corridors.

Työn tarkoitus oli antaa Kolumbian markkinoista kiinnostuneille yrityksille tietoa maan liiketoimintaympäristöstä erityisesti logistiikan näkökulmasta. Jotta Kolumbiaa voitaisiin tarkastella kontekstissaan, maata verrattiin latinalaisamerikkalaisiin verrokkimaihin. Aiheen kannalta merkittävä käsite on trade and transport facilitation (TTF) eli kansainvälisen kaupan ja kuljetusten edistäminen, millä tarkoitetaan rajat ylittävien kuljetusten tehokkuuden parantamista ja kustannusten pienentämistä. Tämä käsite sekä valtioiden edistymistä alalla arvioivat mittarit ovat pääosassa työn teoreettisessa viitekehyksessä. Lisäksi tarkastellaan aiempia tutkimuksia logistiikan suorituskyvystä. Tutkimuskirjallisuudesta voitiin tunnistaa kaksi tekijää, jotka vaikuttavat maiden logistiikan suorituskykyyn: kuljetusinfrastruktuuri ja instituutiot. Näiden tekijöiden laatua mittaavia indikaattoreita käytettiin tässä tutkimuksessa liiketoiminta- ja logistiikkaympäristön analysoimiseen. Tutkimusote on deskriptiivinen ja kvalitatiivinen, sillä tavoite oli laatia yksityiskohtainen kuvaus Kolumbian liiketoimintaympäristöstä logistiikan näkökulmasta. Tutkimuksen viitekehys on ainutlaatuinen, sillä Kolumbian ja verrokkimaiden arvioinnissa käytettiin useampia TTF-mittareita kuin aiemmissa tutkimuksissa. Lisäksi analyysia täydennettiin tarkemmalla katsauksella Kolumbian kuljetussektoriin. Tutkimusaineistona käytettiin lähinnä kansainvälisten järjestöjen ja Kolumbian ministeriöiden laatimia tilastoja, arviointityökaluja ja raportteja. Valtaosa tutkimusaineistosta ulottuu vuoteen 2020. Vaikka Kolumbian liiketoimintaympäristö on Latinalaisen Amerikan parhaita, maan heikkouksia ovat maantie- ja rautatieinfrastruktuuri, tullimuodollisuudet, korruptio ja rikollisuus. Lento- ja meriliikenneyhteydet sekä satamainfrastruktuuri sitä vastoin ovat ensiluokkaisia. Yhdysvaltain markkinat ovat nopeiden lentoyhteyksien päässä. Kolumbialla on etunaan myös sekä Atlantille että Tyynellemerelle ulottuva rannikko ja laaja jokiverkosto. Tyynenmeren puoleinen infrastruktuuri on kuitenkin puutteellinen eikä jokien tarjoamia mahdollisuuksia ole täysin hyödynnetty. Mittavia projekteja on kuitenkin suunniteltu toteutettavaksi 2020-luvulla, kuten jokien kuljetuskapasiteetin lisääminen sekä käytöstä poistettujen rautatieosuuksien käyttöönotto intermodaalikuljetusten tehostamiseksi.
Keywords: trade and transport facilitation, business environment, logistics performance, transport infrastructure, institutional quality, Colombia, Latin America